Impact of Online Learning Modules on Medical Student Microbiology Examination Scores - Johnson, Mary T. (American Society of Microbiology, 2008)
Medical students have a limited amount of time in which to acquire working knowledge of an enormous amount of information, and this is especially relevant for microbiology. One large midwestern medical school is unique in having medical microbiology taught at nine regional campuses using a single core curriculum. A committee of statewide course directors writes a licensure board-style final examination that is referenced to the core and used at all campuses. To prepare for the final examination, students traditionally utilize print-based board examination review books. The purpose of the present study was to determine whether students who train using web-based quizzes score differently as a group on this statewide examination than students who do not utilize the materials online for exam preparation. The study included 71 learners from two different campuses who were taught by the same instructor and were admitted to medical school with similar exemplary credentials. Results were aggregated for three consecutive years. A standard medical microbiology textbook was used to assign the same suggested readings for all students and similar laboratory sessions were provided for all learners. The independent variable was use of the web-based quizzes to prepare before examinations, as indicated by student web usage logs. The dependent variable was score on the statewide final examination. Results support the hypothesis that students who use preparation modules online score higher on the final examination than students who do not. Moreover, students who prepared online scored higher on questions designed to test synthesis of knowledge and analysis of data. The significant difference in final examination outcome (P < 0.002 using a two-tailed unpaired t test) indicates that online preparation for high-stakes examinations could improve student performance in medical microbiology.